A Comparative Study of Types of Nouns in English and Karakalpak Languages - Uteshova Z. X; Allanova M.M (Zeta Repository, 2023)
A noun is a word which is used as the name to person, thing, animal, place, quality, and characteristic, person which is the fact that it is met in everywhere whether in written or spoken language. The goal of the current study is to compare and contrast the categories of nouns in English and Karakalpak to identify their differences. The findings indicate that both languages share certain unique and comparable characteristics.